2012
DOI: 10.1038/ajg.2012.197
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Symptoms Itemized in the Reflux Disease Questionnaire Are Associated With Attenuated Heartburn Response to Acid Suppression

Abstract: Other concomitant RDQ items, particularly "substernal pain" or "dyspepsia-pain", were associated with a reduced treatment effect of acid suppression on "substernal burning". These findings support the use of a more comprehensive assessment of disease state and treatment response in GERD trials and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…However, this study demonstrated approximately a quarter of patients with GORD still had frequent regurgitation, despite heartburn relief. This is in line with the findings of two other studies derived from this dataset5 6 reporting that the responsiveness of individual GORD symptoms was not equivalent and that regurgitation was not as responsive as heartburn to potent acid suppression. These data suggest that persistent regurgitation may be a relatively common characteristic of patients with GORD who do not respond fully to therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, this study demonstrated approximately a quarter of patients with GORD still had frequent regurgitation, despite heartburn relief. This is in line with the findings of two other studies derived from this dataset5 6 reporting that the responsiveness of individual GORD symptoms was not equivalent and that regurgitation was not as responsive as heartburn to potent acid suppression. These data suggest that persistent regurgitation may be a relatively common characteristic of patients with GORD who do not respond fully to therapy.…”
Section: Discussionsupporting
confidence: 92%
“…However, a recent systematic review4 and a retrospective analysis of data from two large GORD clinical trials (conducted using the same dataset as this study)5 suggest that regurgitation typically responds less well than heartburn to acid suppression. These two GORD trials used the Reflux Disease Questionnaire (RDQ) to characterise upper gastrointestinal symptoms and found that the average study subject endorsed four of the six RDQ items with some severity and that the response of heartburn (substernal burning behind the breastbone) was diminished by the presence of concomitant symptoms (particularly dyspepsia) at the start of treatment 6. Another limitation of existing clinical data pertains to the impact of persistent symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, higher pretreatment scores for dyspeptic symptoms predict poorer symptom response to PPI therapy [26]. In two large randomized trials using the Reflux Disease Questionnaire (RDQ) other concomitant RDQ items, particularly ‘substernal pain’ and ‘dyspepsia pain’ were associated with a reduced benefit of acid suppression for ‘substernal burning’ [27]. Finally, there are no specific data supporting the clinical use of questionnaires as a diagnostic test in patients with therapy-resistant GERD.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Reflux Disease Questionnaire(44), UCLA SCTC GIT 2.0(5), Quality of Life in Reflux and Dyspepsia (QOLRAD)(45). …”
Section: Imaging Modalitiesmentioning
confidence: 99%